Upaya Hukum Perdata Terhadap Putusan Pengadilan Yang Belum Memuaskan Pihak Berperkara - Yuliska., Edwin (Fakultas Hukum Universitas Tamansiswa Padang, 2023)
Civil procedural law is a series of regulations that contain how people must act before a court that is regulatory and coercive through a panel of judges, which aims to carry out legal action in civil cases. So parties who reject the results of the court's decision can file legal action and the case can be re-examined at a higher judicial level. Legal remedies for civil cases consist of ordinary legal remedies, namely Resistance (verzet), Appeal, Cassation and extraordinary legal remedies, namely Derden Verzet (Third Party Resistance), Judicial Review, where the legal subjects are humans and legal entities.